The prognostic biomarker L-homoarginine is a substrate of the cationic amino acid transporters CAT1, CAT2A and CAT2B - Chafai, Anja; Fromm, Martin; König, Jörg; Maas, Renke (Scientific Reports, 2017)
Low plasma concentration of L-homoarginine is an independent predictor of cardiovascular events and total mortality. Experimental data indicate that supplementation of L-homoarginine may have protective effects. We aimed to elucidate the mechanisms involved in the cellular uptake of L-homoarginine, which are little understood, so far. Using human embryonic kidney (HEK293) cell lines stably overexpressing the human cationic amino acid transporters CAT1 [solute carrier family 7 (SLC7A1)], CAT2A (SLC7A2A) or CAT2B (SLC7A2B) we assessed the transport kinetics of L-homoarginine and interactions with the CAT substrates L-arginine and asymmetric dimethylarginine (ADMA). Significant uptake of L-homoarginine was observed for all three CATs with apparent KM-values of 175 ± 7 µM for CAT1 and 523 ± 35 µM for CAT2B. Saturation of CAT2A-mediated L-homoarginine uptake could not be reached. Uptake of L-homoarginine by any of the three CATs could be inhibited by L-arginine and ADMA. Significant inhibition of CAT1-mediated uptake of L-homoarginine by L-arginine already occurred in the physiological concentration range. Taken together these data demonstrate that L-homoarginine is a substrate of CAT1, CAT2A and CAT2B and that CAT1 is a key site with regard to physiological relevance and interactions with related substrates such as L-arginine.
EVALuna2:32821